Osseointegration of Extremity Prostheses: A Primer for the Plastic Surgeon. Issue 6 (December 2020) - Souza, Jason M.; Mioton, Lauren M.; Harrington, Colin J.; Potter, Benjamin K.; Forsberg, Jonathan A.
Abstract : Summary: Interest in amputation surgery has increased in conjunction with rising public awareness about amputee care. To date, plastic surgeons have impacted the quality of life and functional potential of amputees through novel strategies for sensory feedback and prosthesis control and various techniques for neuroma treatment and prevention. Osseointegration, which involves the direct skeletal attachment of a prosthesis to bone, has the ability to further maximize amputee function. There exists a critical role for plastic surgeons to help optimize techniques for extremity osseointegration through improved wound care and soft-tissue management. An overview of current osseointegrated prostheses and their associated limitations, and potential avenues through which plastic surgeons can help mitigate these challenges, are discussed in this article.